Rewriting the Atlantic archipelago: modern British poetry at the coast - Jones, Philip (2018)
Despite a so-called ‘oceanic turn’, there has been relatively little attention paid to literary representations of the shoreline as a specific material and cultural site. This thesis examines how modern British poets respond to and represent the coastline in their work, with particular emphasis on notions of place and geographic scale. Whilst looking at the use of the archipelago in recent cultural and literary studies of British and Irish writing, this thesis argues for a more refined and complex sense of the archipelagic, one which responds to the needs and demands of an increasingly global and interconnected world. To better understand this relationship between text and coastal landscape, the project draws on the work of Henri Lefebvre and Doreen Massey, as well as Edward Casey’s investigations into the future of place and Philip E. Steinberg’s reconceptualisation of ocean spaces.